Dual vs. Single Tasking During Circular Walking: What Better Reflects Progression in Parkinson's Disease? - Micó-Amigo, M. Encarna; Kingma, Idsart; Heinzel, Sebastian; Nussbaum, Susanne; Heger, Tanja; Lummel, Rob C. van; Berg, Daniela; Maetzler, Walter; Dieën, Jaap H. van (Frontiers in Neurology, 2019)
Background and aim: Reliable, valid, and sensitive measures of dual-task-associated impairments in patients with Parkinson’s disease (PD) may reveal progressive deficits unnoticed under single-task walking. The aim of this study was to quantitatively identify markers of progressive gait deficits in idiopathic PD while walking over a circular trajectory condition in single-task walking and in different dual-task conditions: (1) circular walking while checking boxes on a paper sheet as fast as possible and (2) circular walking while performing subtraction of 7 as fast as possible. In addition, we aimed to study the added value of dual-tasking assessment over single (circular) walking task assessment in the study of PD progression. Methods: The assessments were performed every 6 months over a (up to) 5 years period for 22 patients in early-stage PD, 27 patients in middle- stage PD and 25 healthy controls (HC). Longitudinal changes of twenty-seven gait features extracted from accelerometry were compared between PD groups and HCs using generalized estimating equations analysis, accounting for gait speed, age and levodopa medication state confounders when required. In addition, dual-task-interference with gait and cognitive performance was assessed, as well as their combination. Results: The results support the validity and robustness of some of the gait features already identified in our previous work as progression markers of the disease in single-task circular walking. However, fewer gait features from dual-task than from single-task assessments were identified as markers of progression in PD. Moreover, we did not clearly identify progressive worsening of dual-task-interference in patients with PD, although some group differences between early and middle stages of PD versus the control group were observed for dual-task interference with the gait task and with the concurrent tasks. Conclusions: Overall, the results showed that dual-tasking did not have added value in the study of PD progression from circular gait assessments. Our analyses suggest that while single-task walking might be sensitive enough, dual-tasking may introduce additional (error) variance to the data and may represent complex composite measures of cognitive and motor performance.